2015
DOI: 10.1111/jfpp.12657
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Mangiferin by High Pressure Liquid Chromatography; Physicochemical and Sensory Evaluation of Functional Mangiferin Drink

Abstract: The current research project was an attempt to extract and quantify mangiferin contents from mango peel and to evaluate its storage stability in functional drinks. The reverse phase high performance liquid chromatography quantification revealed that highest mangiferin contents were observed in ethanolic extracts of chaunsa (7.2 ± 0.2 mg/g) while other varieties like anwar ratol, langra, dusahri and desi mango were lower in mangiferin contents. Moreover, mangiferin ethanolic extract from chaunsa peel showed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Among many natural antioxidants reported, mangiferin the major component of mango peel extract−has been known to possess the potent protective effects against the diseases associated with oxidative stress, such as diabetes and cancer [8,9] (Figure 1). The present authors also demonstrated the antioxidant activity of mangiferinin a previous report [10] . There are many research reports on the beneficial effects of mango fruits [11] , in particular, antioxidant activity.…”
Section: Introductionsupporting
confidence: 87%
“…Among many natural antioxidants reported, mangiferin the major component of mango peel extract−has been known to possess the potent protective effects against the diseases associated with oxidative stress, such as diabetes and cancer [8,9] (Figure 1). The present authors also demonstrated the antioxidant activity of mangiferinin a previous report [10] . There are many research reports on the beneficial effects of mango fruits [11] , in particular, antioxidant activity.…”
Section: Introductionsupporting
confidence: 87%
“…Mangiferin and its extracts have been explored as antioxidant and functional additives for food industries. Imran et al [54] used the agroindustrial mango waste as source of mangiferin to prepare functional drinks, while Boonnattakorn et al [55] added mangiferin to ethylene vinyl acetate matrix in order to obtain an antioxidant packaging for food products. On the other hand, mangiferin is a recognized anticancer compound from mango; its properties have been reported and discussed by several studies.…”
Section: Resultsmentioning
confidence: 99%
“…Mangiferin was found in all fractions (µg/g): FP (1259; 53%) > AKP (967; 40%) > AP (157; 7%). This xanthone is present in leaves, stems, bark, and fruits of the mango tree, but it is also widely distributed in other plants from the Anacardiaceae and Gentianaceae families [ 23 , 24 ]. Mangiferin is a heat-stable molecule, and, unlike more common O -glycosides, it is relatively resistant to hydrolysis of its aglycone (noratiriol) and sugar moieties, which explains why it was detected even after alkaline and acid hydrolysis in the present study.…”
Section: Resultsmentioning
confidence: 99%